Development of Xanthomonas fragariae populations and disease progression in strawberry plants after spray‐inoculation of leaves. (25th June 2013) - Kastelein, P.; Krijger, M.; Czajkowski, R.; van der, P. S.; van der, R.; Jalink, H.; van der, J. M.
<x xml:space="preserve">Abstract</x> Xanthomonas fragariae is the causative agent of angular leaf spot disease of strawberry. Greenhouse experiments were conducted using a X. fragariae isolate tagged with a green fluorescent protein (GFP) for detailed population dynamic studies in and on leaves after spray‐inoculation. The GFP‐tagged bacteria were monitored with dilution plating of leaf washings and leaf extracts, and analysis of intact leaves using a non‐invasive monitoring system called PathoScreen, based on laser radiation of fluorescent cells in plant tissues and signal recording with a sensitive camera. PathoScreen was also used to monitor bacteria grown on an agar medium after leaf printing. During the first 3 days after inoculation, bacterial populations washed off leaves rapidly decreased by at least a factor of 1000, after which populations remained stable until 14 days post‐inoculation (dpi), when symptoms first started to appear. Thereafter, populations increased to a level of 1012 colony‐forming units (CFU) g−1 of leaf material or higher. Similarly, densities in leaf extracts were low during the first 3 days after inoculation, at a level of 100–1000 CFU g−1 of leaf tissue. Gradually populations increased to a level of 109–1012 CFU g−1 at 28 dpi. Higher densities of epiphytic populations were found on the abaxial side than on the adaxial leaf side during the first 2 weeks after inoculation. After spray‐inoculation of leaves, bacterial populations released from infected plants remained low until symptoms appeared, after which plants became highly infectious, in particular under high humidity.